Kazakhstan and GCC: Islamic component in joint collaboration - Issaliyeva, Axamal; Ospanova, Aigerim N.; Alibekuly, Akzhigit; Ilyassova, Zibagul S.; Khazhmuratova, Aigul M. (Opción, 2019)
This article is about features of the Islamic factor in collaboration between Kazakhstan and Gulf Cooperation Council (GCC) countries (Saudi Arabia, UAE, Bahrain, Kuwait, Oman and Qatar). The main focus of our research will be directed to the analysis of Arabic and Kazakh texts with using methods of content-analysis, discourse-analysis and interview. The article compares the significance of the Islamic component for both Kazakhstan and GCC countries. Common points and opposites in the views of Kazakhstan and Arab experts have been revealed. On the basis of which conclusions and recommendations on further improvement of cooperation are provided.